"And lead us not into temptation": Presentation formats and the choice of risky alternatives - Franca Glenzer; Helmut Gründl; Christian Wilde (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2014)
This paper uses laboratory experiments to provide a systematic analysis of how different presentation formats affect individuals' investment decisions. The results indicate that the type of presentation as well as personal characteristics influence both, the consistency of decisions and the riskiness of investment choices. However, while personal characteristics have a larger impact on consistency, the chosen risk level is determined more by framing effects. On the level of personal characteristics, participants' decisions show that better financial literacy and a better understanding of the presentation format enhance consistency and thus decision quality. Moreover, female participants on average make less consistent decisions and tend to prefer less risky alternatives. On the level of framing dimensions, subjects choose riskier investments when possible outcomes are shown in absolute values rather than rates of return and when the loss potential is less obvious. In particular, reducing the emphasis on downside risk and upside potential simultaneously leads to a substantial increase in risk taking.
Keywords: 330; Behavioral finance; Decision under risk; Framing effects